Protecting medical images with biometric information - Fornazin, Marcelo [UNESP]; Netto, Danilo B.S. [UNESP]; Cavenaghi, Marcos Antônio [UNESP]; Marana, Aparecido Nilceu [UNESP] (Springer Nature, 2008)
Medical images are private to doctor and patient. Digital medical images should be protected against unauthorized viewers. One way to protect digital medical images is using cryptography to encrypt the images. This paper proposes a method for encrypting medical images with a traditional symmetric cryptosystem. We use biometrics to protect the cryptographic key. Both encrypted image and cryptographic key can be transmitted over public networks with security and only the person that owns the biometrics information used in key protection can decrypt the medical image. © Springer Science+Business Media B.V. 2008.
Keywords: Biometric informations; Biometrics informations; Cryptographic key; Digital medical images; Encrypted images; Key protections; Public networks; Symmetric crypto systems; Biometrics; Software engineering; Cryptography